Disrupsi Teknologi dalam Akuntansi: Antara Automasi, Efisiensi, dan Redefinisi Profesi Akuntan - Atika Syahra; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Technological disruption has transformed the accounting landscape through the integration of artificial intelligence, robotic process automation, cloud accounting, and big data analytics that reshape organizational processes and professional structures. This study examines how technological transformation reconstructs accounting practices, operational efficiency, and the professional identity of accountants within the digital economy. The research employed a qualitative non empirical approach based on library research through the synthesis of academic literature related to digital accounting transformation. The findings indicate that automation improves efficiency, reporting accuracy, and integrated control systems while simultaneously generating risks associated with cybersecurity and ethical governance. The study concludes that the sustainability of the accounting profession increasingly depends on adaptive competencies, technological literacy, and multidisciplinary capabilities aligned with the dynamics of Society 5.0.